Determination of silicon concentration in some horticultural plants - Hogendorp, Brian K.; Cloyd, Raymond A.; Swiader, John M. (My University, 2013)
Although silicon is not an essential element, it is taken up by plants but is rarely quantified. Therefore, this study quantified the silicon concentration in 10 commonly grown horticultural plants including meadow sage (Salvia x sylvestris), tickseed (Coreopsis verticillata), garden phlox (Phlox paniculata), New England aster (Symphyotrichum novae-angliae), Chinese astilbe (Astilbe chinensis), coral flower (Heuchera hybrid), garden zinnia (Zinnia elegans), French marigold (Tagetes patula), sweet basil (Basil spp.), and rosemary (Rosmarinus officinalis) using a plant alkaline fusion technique, which involved dry-ashing plant tissue samples and measuring color development with a spectrophotometer. Both zinnia and aster accumulated substantially more silicon from the municipal water source and growing medium (5365 and 4797 mg·kgˉ¹ silicon, respectively) than the other plants evaluated, which had concentrations less than 2500 mg·kgˉ¹ silicon. This study is just one of a few in which the silicon concentration in various horticultural plants has been quantified. Consequently, this may lead to better understanding those plants that will or will not benefit from applications of silicon-based fertilizers to promote cold-hardiness and/or plant resistance to fungal pathogens and insect pests.
Citation: Hogendorp, Brian K., Raymond A. Cloyd, and John M. Swiader. 2012. “Determination of Silicon Concentration in Some Horticultural Plants.” HortScience 47 (11): 1593–95. https://doi.org/10.21273/HORTSCI.47.11.1593.
Keywords: Silicon-fertilizer; Potassium–silicate fertilizer; Quantification technique; Greenhouse; Horticulture